Novel Pt-Ni/NiO/Ni2O3 based electrodes for electrocatalytic biodiesel production from waste palm oil. (2020) - Sarno, M.; Ponticorvo, E.; Scarpa, D.
Abstract: Here, the synthesis, using a simple and easy-scalable procedure, of a Pt-Ni/NiO/Ni2 O3 nano-structured catalyst for the electro-assisted production of biodiesel from methanol and waste cooking palm oil is reported. After synthesis, the as-obtained nanomaterial was broadly characterized: TEM images, showed the existence of a nanohybrid with a quasi-spherical morphology consisting of platinum nanoparticles (2–3 nm) anchored to Ni/NiO/Ni2 O3 nanoparticles (50 nm); XRD, TG, DTG, Raman and FT-IR analyses confirmed the obtained result. Afterward, the nanohybrid was tested for the electro-production of biodiesel at a low voltage value (10 V) and at low temperature (40 °C). The transesterification reaction efficiently occurred with a reduced amount of nanocatalyst in a two-phase system under strong magnetic agitation and without adopting toxic co-solvents. The effects of the reaction time, NaCl content and methanol/oil molar ratio on the methyl esters yield were studied, and the reaction products were analysed. In particular, it was observed that by using a waste palm oil treated for 7 days at 240 °C as feedstock, even after 60 min of reaction, a yield of >50% was reached. A yield value of ∼96% was eventually reached after 3 h of reaction.